EFEKTIVITAS MEDIA MAGICAL FLASH CARD DALAM MENINGKATKAN KOSA KATA LITERASI DASAR SISWA KELAS 1 SDN SEMEN - Komariah Komariah; Bernadus Wahyudi Joko Santoso Santoso; Haryadi Haryadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Vocabulary knowledge is crucial for students' ongoing learning, yet it often faces numerous obstacles in improving it. One reason is the low literacy skills of students, especially in first-grade elementary school. This study aims to examine the significance of the use of Magical Flash Cards in improving the basic literacy vocabulary of first-grade students at Semen Elementary School. The research question addresses the need to improve students' basic literacy vocabulary through measurable learning interventions. This study used a quantitative approach with a One Group Pretest-Posttest design, involving a sample of 20 students selected using a purposive sampling technique. Data were collected using test instruments (pretest and posttest) and analyzed statistically. The Shapiro-Wilk normality test showed a normally distributed data (p=0.124). A Paired Sample t-test demonstrated a convincingly significant difference between pretest and posttest scores (p < 0.05). Normalized Gain (N-Gain) analysis showed an average increase of 0.65, categorized as moderately effective. These results prove that the Magical Flash Card media applied is effective in improving students' basic literacy vocabulary skills.